The Effect of BI Interest Rate and Exchange Rate on Profitability at PT. Pegadaian Tbk (Period 2017-2024) - Rosviantini, Nova; Adhianto, R Deden (International Journal of Management and Business, 2025)
This study seeks to analyze the impact of the Bank Indonesia interest rate and currency rate on the profitability of PT. Pegadaian Tbk from 2017 to 2024. The employed research methodology is quantitative, utilizing population data that includes the Bank Indonesia interest rate, the US Dollar exchange rate, and the Return on Assets (ROA) of PT. Pegadaian Tbk. The sample was chosen using purposive sampling from 2017 to 2024. The study's results suggest that, to some extent, the Bank Indonesia interest rate and exchange rate do not significantly impact the profitability of PT. Pegadaian Tbk. Moreover, concurrent data indicate that neither variable affects the company's profitability. The data indicate that variations in interest and exchange rates do not immediately affect PT. Pegadaian Tbk's profitability.